Orobanche apuana (Orobanchaceae) a new species endemic to Italy - Domina, Gianniantonio; Soldano, Adriano (Phytotaxa, 2015)
Orobanche apuana, a new species belonging to Orobanche sect. Orobanche, is described and illustrated from the Apuan Alps, Central Italy. Its relationships with the other species of the group of O. caryophyllacea (O. grex Galeatae) and with other Orobanche that parasitize Santolina species are examined. The names Boulardia latisquama, Orobanche lutea and O. teucrii are here lectotypified.